Effect of relative humidity at chronic temperature on growth performance, glucose consumption, and mitochondrial ATP production of broilers - Ying ZHOU; Min-hong ZHANG; Jing-hai FENG; Hua-jie DIAO (Journal of Integrative Agriculture, 2019)
An experiment was conducted to investigate the effect of relative humidity (RH) at chronic temperature on growth performance, glucose consumption, and mitochondrial adenosine triphosphate (ATP) production of broilers. A total of 180 28-day-old Arbor Acres broilers (half males and half females) were randomly allocated to three treatments, each containing six replicates of 10 birds per treatment, using a completely randomized design. Birds were reared at 35, 60 or 85% RH at 32°C for 15 days (temperature increased by 3°C every 3 days from 20 to 32°C within 15 days: 20−23−26−29−32°C). RH affected (P<0.05) average daily feed intake (ADFI), average daily gain (ADG), average daily water consumption (ADWC), blood glucose concentrations, muscle glycogen levels, avian uncoupling protein (av UCP) mRNA expression, and cytochrome c oxidase (CCO) activity in liver of broilers at 42 days of age. The 85% RH decreased (P<0.05) ADFI, ADG and ADWC; 35% RH decreased (P<0.02) ADG. Both 85 and 35% RH increased (P<0.01) blood glucose and decreased (P<0.05) muscle glycogen. Both 85 and 35% RH increased (P<0.05) av UCP mRNA expression. 35% RH decreased (P<0.05) CCO activity. In conclusion, both high and low RH inceased glucose consumption and reduced mitochondrial ATP poduction, leading to a decline in growth rate.